Prevalence and Clinical Features of Thalassemia Minor Cases - Muhammad Faizan, Nadia Rashid, Sumbal Hussain, Ansa Khan, Jamshid Khan, Salma Zeb, Sardar Qaser Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thalassemia, the most common heterogeneous single gene disorder causing sever genetic health problem in the world. In 1932 George and William gave it the name thalassemia derived from Greek words (“thallassa: mean sea) and (“aima: mean blood). The research was conducted on thalassemia minor patients in North Waziristan and some selected areas of Peshawar Khyber pakhtunkhwa. Methods: During this survey 100 thalassemia minor patients were interviewed belonging to different castes. It was observed that majority of the patients were from the age group 1-10 years both in male asn females. Different ethnic groups were interviewed such as Yousafzai, Halimzai, Dawar, Wazir, Noor khel, Musazai, Saidan, Miserkhal, Afridi, Miagan, and Afghan. Results: The most of the thalassemia minor patients belonged to rural area (62.4 %) while 36.6% patients were reported from urban area. The maximum number of thalassemia minor patients belonged to lower class which was reported 47% followed by middle class (35%) and rich people (18%). The parents of 64 patients were cousin while the parents of 36 patients had marriage out of the family. The birth abnormalities were also recorded and observed as abortion (30%), delay birth (23%), still birth (13%) and premature birth (17%). During this study it was observed that majority of the patients were of the moderate body status (54.5%) Interestingly the ratio of obese people was very low. While the ratio of thin people was 39.4%. The physical abnormalities found in thalassemia minor patients included eye, skin, ear, mental and bone and joint abnormalities. the people having the age from 1-10 have an average HB level of 9.45 g/dl while those having age of 41-60 have an average HB level of 11.58 g/dl. The physical infections also reported such as eye infection (39%), GIT infection (20%), Lung infection, Skin infection (16%), UTI (7%) and Ear infection (2%). Conclusion: This study provides an insight in to the mechanism of transmission of thalassemia in the family and suggest social awareness about the disadvantages of the interfamilial marriages. Keywords: Thalassemia, Consanguineous marriages, Hemoglobin, Birth Abnormalities, Infections.